Factors Affecting Potato Marketed Surplus in Kavre District of Nepal - Kharel, Meena (International Journal of Applied Sciences and Biotechnology, 2022)
Potato is a staple food crop. It has been being a highly consumed food grown in all parts of Nepal. A study was conducted to identify the factors affecting the potato marketed surplus, taking randomly selected 100 potato growing households in Kavre district of Nepal. Face to face survey with semi structured questionnaire for primary data collection and secondary information was collected through review of relevant publications from the government authority. Descriptive statistics and econometric model were used for data analysis. The multiple linear regression model was used to identify the determinants of potato marketed surplus. It was revealed around 81% of the total potato production was usually sold to the market and the remaining 11% and 9% of potato were used for seed and home consumption respectively. The multiple regression model indicates that among the seven variables used namely area of potato production, NARC released potato varieties, experience of farmer, education level, price and selling to traders were significantly influenced to the marketed surplus of potato in Kavre. Farmers’ access to quality inputs services and capacity building training for enhanced production and strengthening backward and forward linkage for effective marketing.